Evaluasi Efisiensi dan Efektivitas Penggunaan Tenaga Outsourcing di Untag Banyuwangi dari Perspektif Transaction Cost Economics - Yovita Vivianty Indriadewi Atmadjaja; Ni Kadek Yuliandari; Kurnia Riesty Utami (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The education sector, especially higher education or universities, has a foundation that must be carried out, is called the Tri Dharma University whose focus on Teaching, Research and Community Service. In addition to this, in order to maximally support lecturers in carrying out the Tri Dharma University, other activities such as service to students need to be assisted by other parties. The other activities intended are in terms of security and cleanliness within the University. In order to carry out activities in a conducive manner, some parties choose to use third party services or outsourcing. This study aims to evaluate the strategy of outsourcing in terms of the theory of Transaction Cost Economics at the University of August 1945 Banyuwangi. The research method in this research uses qualitative research methods with research informants who are choosed purposively. The selected informants are informants who are considered to be involved and affected by the implications of implementing the outsourcing system, including the implementing agency and the owner of the designated outsourcing agency. Based on the results of the study it is known that the cost analysis in terms of TCE theory, the use of outsourced labor at Untag Banyuwangi is considered inefficient. This is because the costs arising from using outsourcing services are considered to be more expensive than before using outsourcing services. However, things are different when viewed in terms of asset specificity consisting of human resources (skill level, knowledge, and experience of employees), physical assets, location, dedicated, temporal, and brand specificity, it can be concluded that Untag Banyuwangi has been effective and efficient in the use of outsourcing services. So that the University of 17 August 1945 Banyuwangi does not need to provide increased employee skill training.